2007
DOI: 10.1111/j.1530-0277.2007.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol‐Induced Insulin Resistance Is Associated With Macrophage Infiltration Into Adipose Tissue and Altered Expression of Adipocytokines

Abstract: These data demonstrate that chronic ethanol feeding results in the development of insulin resistance, associated with impaired insulin-mediated suppression of hepatic glucose production and decreased insulin-stimulated glucose uptake into adipose tissue. Chronic ethanol-induced insulin resistance was associated with increased macrophage infiltration into adipose tissue, as well as changes in the expression of adipocytokines by adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 39 publications
(69 reference statements)
5
103
0
1
Order By: Relevance
“…The development of adipose tissue inflammation in obese animals is associated with an increase in body weight and adipocyte size (33). In contrast, ethanol feeding is not associated with increased body weight, adiposity, or adipocyte size (3,5), suggesting that adipose inflammation in response to ethanol is initiated via a mechanism(s) distinct from those involved in obesity-induced adipose inflammation. Ethanol metabolism via CYP2E1 increases oxidative stress and is a well studied contributor to alcoholic liver disease (12).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The development of adipose tissue inflammation in obese animals is associated with an increase in body weight and adipocyte size (33). In contrast, ethanol feeding is not associated with increased body weight, adiposity, or adipocyte size (3,5), suggesting that adipose inflammation in response to ethanol is initiated via a mechanism(s) distinct from those involved in obesity-induced adipose inflammation. Ethanol metabolism via CYP2E1 increases oxidative stress and is a well studied contributor to alcoholic liver disease (12).…”
Section: Discussionmentioning
confidence: 81%
“…6). Ethanol exposure is associated with the development of oxidant stress in a number of tissues (12) including adipose tissue (3,4). In the liver, ethanol-induced oxidant stress is due at least in part to ethanol metabolism via CYP2E1 (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperinsulinemic-euglycemic clamps were then performed on one rat at a time as previously described (17), with minor modifications. Data on the effects of chronic ethanol on glucose disposal during these specific clamp studies have been previously reported (18). Briefly, rats were transported from the Animal Resource Center and allowed at least 90 min to stabilize before commencement of the glucose clamp.…”
Section: Methodsmentioning
confidence: 99%